The Homebrewed Christianity guide to being human : becoming the best bag of bones you can be - Bowman, Donna (Homebrewed Christianity guide., 2018)
This Homebrewed Christianity Guide explores how Christian theology can address our rapidly changing paradigms of human existence. Donna Bowman argues that theology can contribute to our knowledge of the human self as gained through the sciences, that a theological perspective on humanity is useful in contemporary pluralistic and global settings, and that there's theological significance to work and play. She also tackles issues of gender, sexuality, creativity, and human expression--with jokes! It's no longer possible to assign definitive meaning to categories like man and woman, self and society, freedom and determinism, reason and feeling, soul and body by reference to systems of narrative (including biblical narrative) and interpretation in which those ideas are taken for granted. The theology of human personhood begins with irreducible experiences both universal and particular and searches for functional understandings from the whole range of Christian and non-Christian ways of knowing. Plus, jokes!